Perempuan sebagai Pemimpin?: Belajar Nilai Kepemimpinan dari Priska dalam Kehidupan Jemaat Mula-Mula - Paulus Eko Kristianto (Tumou Tou, 2022)
This article examines what we can learn from Prisca's leadership in the life of the early church. This process rests on two key questions, how is Priska's role as a woman who becomes a leader? and what can be learned from Priska? This research was conducted using the feminist hermeneutic method. Feminist hermeneutics provides space for women as the subject of interpretation and designer of meaning after reading. The results of this study indicate that Priska deserves to be a leader. Priska has loyalty and a spirit of service that deserves an example as a leader.